Rivalry : - Nagai Kafu (Columbia University Press, 2007)
Rivalry tells a sweeping story in which sexual politics compete with sisterly affection in a world ruled by material transaction. Komayo is a former geisha who, upon the death of her husband, must return to the "world of flower and willow" to escape poverty. A chance encounter with an old patron, Yoshioka, leads to a relationship in which both lovers hope to profit: Yoshioka believes Komayo can restore his lost innocence; Komayo plans to use Yoshioka's patronage to compete in the elaborate music and dance performances staged by her fellow geisha